The Molecular Mechanisms of Regulatory T Cell Immunosuppression - Pandiyan, Pushpa; Zheng, Lixin; Lenardo, Michael (Frontiers in Immunology, 2011)
CD4+CD25+Foxp3+ T lymphocytes, known as regulatory T cells or Tregs, have been proposed to be a lineage of professional immune suppressive cells that exclusively counteract the effects of the immunoprotective "helper" and "cytotoxic" lineages of T lymphocytes. Here we discuss new concepts on the mechanisms and functions of Tregs. There are several key points we emphasize: 1. Tregs exert suppressive effects both directly on effector T cells and indirectly through antigen-presenting cells (APCs); 2. Regulation can occur through a novel mechanism of cytokine consumption to regulate as opposed to the usual mechanism of cytokine/chemokine production; 3. In cases where CD4+ effector T cells are directly inhibited by Tregs, it is chiefly through a mechanism of lymphokine withdrawal apoptosis leading to polyclonal deletion (PCD); and 4. Contrary to the current view, we discuss new evidence that Tregs, similar to other T cells lineages, can promote protective immune responses in certain infectious contexts (Pandiyan et al. 2011; Chen et al 2011). Although these points are at variance to varying degrees with the standard model of Treg behavior, we will recount developing findings that support these new concepts.